Administration of an organization undergoing change: Some limitations of the transaction cost economics approach. Issue 4 (3rd September 2018) - Chatterjee, Abha; Chanda, Sasanka Sekhar; Ray, Sougata
Abstract : Purpose: This paper aims to develop conceptual arguments questioning the efficacy of administration by the transaction cost economics (TCE) approach in an organization undergoing a major change. Design/methodology/approach: The focus is on three distinct dimensions of organizational life where, as per prior research, TCE is likely to be inadequate: interdependence across transactions, high reliance on managerial foresight and inseparability of administrative decisions made at different points in time. Findings: The climate of coercion and surveillance engendered by administration based on TCE approaches – that punishes deviation from goals, even when they are framed on inadequate knowledge – forestalls creative problem-solving that is necessary to address unforeseen developments that arise during change implementation. Fiat accomplishes within-group compliance in the change project sub-teams, but between-group interdependencies tend to be neglected, hampering organizational effectiveness. Moreover, attempts to create independent spheres of accountability for concurrent fiats regarding pre-existing and new commitments breed inefficiency and wastage. Research limitations/implications: The malevolent aspects of TCE-based administration contribute to organizational dysfunctions like escalation of commitment and developing of silos in organizations. Practical implications: To succeed in effecting a major organizational change, meaningful relaxation of demands for delivering on prior goals is required, along with forbearance of errors made during trial-and-error learning. Originality/value: TCE-based administration is deleterious to an organization attempting a major change. Supremacy accorded to resolution of conflicts in distinct hierarchical relationships by the mechanism of fiat fails to address the needs of an organizational reality where multiple groups are engaged in a set of interdependent activities and where multiple, interdependent organizational imperatives need to be concurrently served.